Dampak Digital Marketing dan Electronic Word of Mouth terhadap Keputusan Pembelian Produk Skincare Skintific di Batam - Ratri Perwinta Nengsi; Inda Sukati (IPM2KPE, 2024)
This research aims to investigate the influence of digital marketing and electronic word of mouth variables on purchasing decisions for skincare products in Batam. This research uses the Jacob Cohen formula to determine the sample size, with a total of 204 respondents because the sample size is unknown. The data was processed using SPSS version 25 software. The research results showed that digital marketing and electronic word of mouth partially had a positive and significant effect on purchasing decisions for skincare products. Apart from that, simultaneously, these two variables also have a positive and significant influence on the decision to purchase skincare products, as proven by the ANOVA test with a calculated f value that is greater than the f table and a significance mark of less than 0.05. This shows the important role of digital marketing and electronic word of mouth in influencing decisions to purchase skincare products. The conclusion is that digital marketing and electronic word of mouth have a significant role, both partially and simultaneously, in influencing skincare product purchasing decisions in Batam. Keywords: Electronic Word of Mouth, Purchasing Decisions, Digital Marketing